Observation of charge-ordering in particle production in hadronic Z(0) decay - Abreu, P; Adam, W; Adye, T; Adzic, P; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andersson, P; Andreazza, A; et al. (1997)
Analysis of the rapidity structure of charge correlations in hadronic events from Z0 decays gives evidence for chain-like charge-ordering of particle production along the thrust axis, as predicted by 'QCD-motivated string-like fragmentation models. © 1997 Published by Elsevier Science B.V.